THE ELEVENTH PLENUM AND FILM CRITICISM IN EAST GERMANY. (9th September 2013) - Brockmann, Stephen
ABSTRACT: This article explores the role of film theory and film criticism in the controversies surrounding the Eleventh Plenum of the Socialist Unity Party (SED), which led to the banning of twelve East German films in 1965–6. It looks at the work of the film critic Fred Gehler in the weekly newspaper Sonntag, and it explores the editorial policies of the journal Filmwissenschaftliche Mitteilungen, which was edited by Heinz Baumert, director of the institute for film scholarship at the Hochschule für Filmkunst in Potsdam, the GDR's only film school. The article looks at the critique that Gehler, Baumert, and others were making of GDR film culture in the mid‐1960s and at the suggestions they put forward for the improvement of East German film. It also examines the negative reaction to this critique surrounding the Eleventh Plenum, and it argues that this negative reaction had a profound impact on the subsequent history of East German cinema, as well as on the development of younger East German filmmakers.